2020
DOI: 10.26434/chemrxiv.12003930.v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Atovaquone, Ouabain and Mebendazole as FDA Approved Drugs Tar-geting SARS-CoV-2 (Version 4)

Abstract: <p>The newly emerged coronavirus, SARS-CoV-2, and the resulting COVID-19 disease, has spread swiftly across the globe since its initial detection in December 2019. Given the heavy toll of this pandemic, therapeutic options for treatment are urgently needed. Here, we adopted a repositioning approach using in-silico molecular modeling to screen FDA-approved drugs with established safety profiles for potential inhibitory effects against SARS-CoV-2. We used structure-based drug design to screen more than 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“… 2 Although the data may be biased by patient selection, treatment indication and residual confounding, including lack of adjustment for socioeconomic status and prehospital medication, this controversial finding merits further investigation. In addition, Farag et al 3 performed a computer-based study and used a structure-based drug design to screen more than 2000 Food and Drug Administration-approved drugs against SARS-CoV-2 main protease enzyme substrate-binding pocket. Other than antiviral drugs, the authors also identified rosuvastatin as a drug that may be useful against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Although the data may be biased by patient selection, treatment indication and residual confounding, including lack of adjustment for socioeconomic status and prehospital medication, this controversial finding merits further investigation. In addition, Farag et al 3 performed a computer-based study and used a structure-based drug design to screen more than 2000 Food and Drug Administration-approved drugs against SARS-CoV-2 main protease enzyme substrate-binding pocket. Other than antiviral drugs, the authors also identified rosuvastatin as a drug that may be useful against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that other potential mast cell mediator release and function-modifying drugs could interact with important pathways in viral replication. In silico docking studies have indicated that the cysteinyl leukotriene (cysLT) receptor antagonist montelukast that is indicated for the treatment of asthma [5,44], the 5-lipoxygenase (5-LOX) inhibitor setileuton [45] and the H 1 receptor antagonists fexofenadine [44], mizolastine and cetirizine [46] interact with M pro , whereas the mast cell stabiliser cromolyn is a potential RdRP inhibitor [5]. Another work highlighted the interaction of montelukast with PL pro [6].…”
Section: Histamine and Covid-19 Bioinformatics/ Drug Repurposing Studiesmentioning
confidence: 99%
“…Structure-based activity studies and various highthroughput studies have identified distinct inhibitors of SARS-CoV and MERS-CoV main proteases (Anand et al, 2003;Bacha et al, 2004;Kumar et al, 2017;Ryu et al, 2010). Therefore, it is crucial to identify novel inhibitors of SARS-CoV-2 main protease to control COVID-19 (Farag et al, 2020;Haider et al, 2020;Wang, 2020). On the other hand, main protease is highly conserved across coronaviruses.…”
Section: Introductionmentioning
confidence: 99%